Workshop on Virtual Museums and Their Educational Applications - Radoslav Pavlov; Desislava Paneva-Marinova; Detelin Luchev; Jordan Stoikov (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2020)
The workshop on Virtual Museums and their Educational Applications presents outcomes of the National Scientific Program “ Cultural and Historical Heritage, National Memory and Social Developmen t”, funded by the Ministry of Education and Science (approved by DCM No 577 of 17 August 2018), achieved during the second year under the Work Package No. 4 “Activities for the Development of Scientific and Applied Products” (Activity "Digitization and virtualization of cultural heritage"). The workshop outlines also some future trends for educational applications of virtual museums.